Desenvolvimento, caracterização e aplicação de filmes comestíveis produzidos com farinha de casca de banana madura e extrato das folhas de Eriobotrya japonica Lindl. - Viviane Dias Medeiros Silva (2020)
The development of edible films based on agri-food residues combined with natural additives is a promising technology in the food industry. Thus, the aim of this study was to develop edible films and coatings based ripe banana peel flour, cornstarch and loquat leaves (Eriobotrya japonica) extract and apply them in mozzarella cheeses. First, banana peel flour was characterized and presented high carbohydrate content and total dietary fiber, significant amount of total phenolics with antioxidant activity, good technological properties and it was possible to suggest the presence of 26 substances by paper spray-mass spectrometry (PS-MS). Then, films with this flour were developed, evaluating the effect of cornstarch concentration and heating time on physical, mechanical and barrier properties. The increase in starch content increased thickness, mechanical strength, elastic modulus, and water vapor permeability of the films. The increase in heating time reduced lightness and increased color intensity and elongation rate of the film. In view of these results, a banana peel flour standard film was developed to be characterized with and without the addition of loquat leaf extract. This extract was obtained by evaluating the influence of leaf dehydration, solvent type and extraction method on total phenolic content and antioxidant and antimicrobial activities. The extracts obtained with the leaves dehydrated at 40 °C, with ethanol and ultrasound, had the best properties and it was possible to suggest the presence of 49 different compounds by PS-MS. This extract was chosen as an additive to be incorporated into the standard film in two concentrations (2 and 4%). The addition of the extract decreased tensile strength, elastic modulus and water vapor permeability. Only in the film containing 4% extract, an increase in color intensity, thickness, elongation, deformation rate and solubility was observed, while the puncture strength decreased. The standard and added extract films were less resistant, but more flexible compared to starch film. With this, the standard formulation and the one containing 4% extract were applied in mozzarella cheeses in pieces by immersion and in slices interleaved with the films, and stored at 4 °C for 28 days. There was weight loss during storage for all treatments. The pH increased and the titratable acidity decreased during storage for both cheeses. The cheeses submitted to coating or film presented lower humidity than controls. The presence of the extract made the cheeses less light and with yellowish color more intense. The hardness of the cheeses has not changed. It is concluded that the use of these edible films and coatings has potential as an alternative material for storage and conservation of cheeses.